The assessment of the influence of the Gumiton organomineral complex on the development of root rot and structural elements of the winter wheat yield - Suslov Aleksey; Sviridenk Dimitry; Mamayev Vasiliy; Sychiova Irina (BIO Web of Conferences, 2021)
It has been shown that pre-sowing treatment increases field germination by 5.5%, and the preservation of plants after overwintering increases by 4.3%. Gumiton strengthened the work of the assimilation apparatus of the flag leaf due to an increase in leaf area by 29.3-49.1% and extended the life of plants. As a part of a tank mixture (Tabu Super, 1.5 l / t + Tertia, 2.5 l t), the drug allowed to reduce the prevalence of the root rot disease to 2.45-1.05% in comparison with the control. The organomineral complex provided the formation of a larger and more leveled grain with a mass of 1000 grains of 47.0-47.5 g, 43.9 g in the control; the grain nature is more than 780 g / dm 3, 751.7 g / dm 3, in the control. The use of Gumiton (seeds + tillering + piping) against the background of N 96 P 96 K 96 provided a high yield increase by 37.8%. To reduce the expenses of foliar fertilization with nitrogen fertilizers, the Gumiton organic-mineral complex should be recommended, since it is an element of greening in intensive technologies of winter wheat cultivation.